2022
DOI: 10.3390/plants11192449
|View full text |Cite
|
Sign up to set email alerts
|

Cold Resistance of Euonymus japonicus Beihaidao Leaves and Its Chloroplast Genome Structure and Comparison with Celastraceae Species

Abstract: Euonymus japonicus Beihaidao is one of the most economically important ornamental species of the Euonymus genus. There are approximately 97 genera and 1194 species of plants worldwide in this family (Celastraceae). Using E. japonicus Beihaidao, we conducted a preliminary study of the cold resistance of this species, evaluated its performance during winter, assembled and annotated its chloroplast genome, and performed a series of analyses to investigate its gene structure GC content, sequence alignment, and nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Research has shown that low temperatures can inhibit the biogenesis and development of chloroplasts during the early greening stage of rice (Oryza sativa L.) seedlings [25]. Atpl and atpE play an important role in the adaptation of species to environmental changes within the Celastraceae family, affecting electron transfer and energy synthesis processes [26]. Tobacco lacking the chloroplast gene petL displays impaired photosynthesis and bleached leaves in cold conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that low temperatures can inhibit the biogenesis and development of chloroplasts during the early greening stage of rice (Oryza sativa L.) seedlings [25]. Atpl and atpE play an important role in the adaptation of species to environmental changes within the Celastraceae family, affecting electron transfer and energy synthesis processes [26]. Tobacco lacking the chloroplast gene petL displays impaired photosynthesis and bleached leaves in cold conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…The water retention capacity of E. japonicus leaves surpasses that of Ligustrum vicaryi among broad-leaved shrub species, thereby enhancing both the aesthetic and functional aspects of landscape through improved soil water storage ( Yin et al., 2008 ). In Beijing, E. japonicus is extensively cultivated as a shrub due to its robust resistance to the dry and cold climatic conditions prevalent in the region, effectively reducing particulate matter during winter ( Cai et al., 2022 ). However, E. japonicus is highly susceptible to fungal diseases such as powdery mildew and anthracnose ( Yao et al., 2018 ; Lin et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%